Are the Eatwell Guide and nutrient profiling models consistent in the UK? - Pinho-Gomes, AC; Kaur, A; Scarborough, P; Rayner, M (MDPI, 2021)
A nutrient profiling model (NPM) was developed in 2005 in the UK to regulate the marketing of foods to children. It was revised in 2018, but the new version has not been finalised. The Eatwell Guide (EWG) is the UK’s official food-based dietary guidelines. The aim of this study was to evaluate the agreement between the 2005 and 2018 versions of the NPM and the EWG. Using recent National Diet and Nutrition Surveys, we estimated the healthiness of individual diets based on an EWG dietary score and a NPM dietary index. We then compared the percentage of agreement and Cohen’s kappa for each combination of the EWG score and NPM index across the range of observed values for the 2005 and 2018 versions. A total of 3028 individual diets were assessed. Individuals with a higher (i.e., healthier) EWG score consumed a diet with, on average, a lower (i.e., healthier) NPM index both for the 2005 and 2018 versions. Overall, there was good agreement between the EWG score and the NPM dietary index at assessing the healthiness of representative diets of the UK population, when a low cut-off for the NPM dietary index was used, irrespective of the version. This suggests that dietary advice to the public is broadly aligned with NPM-based food policies and vice-versa.